The The Associative Influence of Phonetic Nonce Words (Occasionalisms) in Modern Ukrainian Poetical Discourse - Hryshko, Yuliia (Respectus Philologicus, 2022)
The article presents the results of three linguistic associative experiments. The purpose of this research is to determine the influence of specific linguistic units – phonetic nonce words (occasionalisms) – on the perception of modern Ukrainian poetical discourse by addressees (readers). As stimuli for linguistic analysis of phonetic occasional units in modern Ukrainian poetical discourse used the most frequent phonetic nonce words in their graphic actualization (total 16 different stimuli). The three experimentally groups of respondents include 105 students of three Poltava high schools. A result of these experiments are 1684 reactions, among which 1146 (68%) – positive, 300 (18%) – negative, 238 (14%) – neutral. The lowest per cent of neutral reactions is motivated because phonetic nonce words are power intensifiers for the expressiveness of sound background in poetical discourse. The phonetic nonce words positively influence the perception of modern verbal discourse by addressees. The special role in decoding of sound information belongs to acoustic-articulator characteristics of vowels and consonants.
Keywords: phonetic nonce words (phonetic occasionalisms); modern poetical discourse; linguistic associative experiment; acoustic-articulator characteristics of vowels and consonants